Influence Of Customer Experience, Perceived Value, and Trust on Repurchase Intention on BRT Trans Semarang Users - Pramitasari, Vhiela Eka; Karnowahadi, Karnowahadi -; Wiedayanti, Destine Fajar (Politeknik Negeri Semarang, 2024)
Semarang is a region that has provided public transportation facilities such as Bus Rapid Transit (BRT) Trans Semarang. This research examines the influence of repurchase intention by BRT Trans Semarang users. This study uses three variables namely customer experience, perceived value, and trust as determining factors. This research is a quantitative study with a sample size of 112 respondents using the BRT Trans Semarang. by using multiple linear regression analysis tools, the regression equation Y = 4,074 + 0,222X1 + 0,295X2 + 0,239X3 + e is obtained. With the t-test result show that partially customer experience, perceived value, and trust have a significant partial effect on Repurchase Intention by BRT Trans Semarang users. The result of the F test obtained Sig value = 0,000 which show collectively displays the variables of customer experience, perceived vatalue, and trust have a significant effect on repurchase intention. The implications of the results of this research indicate that the Trans Semarang BRT manager is considered to be able to increase trust by maintaining the quality of service to drivers and officers. The affordable prices and good condition of the buses are considered capable of making customers feel satisfied so that they are willing to make repeat purchases when using BRT Trans Semarang.